The effect of self-regulated writing strategies on students' L2 writing engagement and disengagement behaviors. (June 2022) - Zhou, Shiyao Ashlee; Hiver, Phil
Abstract: Self-regulated learning (SRL) is a topic of increasing interest in the field of language learning and instruction. In this study, we set out to investigate the relationship between students' use of SRL strategies in second language (L2) writing, their L2 writing engagement, and L2 writing procrastination. Data were collected from college students in mainland China ( N  = 816) related to their SRL strategy use, L2 writing engagement, and L2 writing procrastination. SRL strategy use for L2 writing was found to be an important predictor of student engagement in their writing class, and results from mediation analyses confirmed a full mediation effect from students' SRL strategy use to L2 writing procrastination through their engagement in L2 writing class. Student engagement in L2 writing class also significantly and negatively predicted students' procrastination in L2 writing. These findings suggest that the use of SRL strategies functions as an important antecedent to student engagement in their writing class, and that these jointly reduce student procrastination in L2 writing. Given the essential role SRL strategy use plays in student engagement in L2 writing classrooms, which in turn reduces student writing procrastination, we discuss the importance of explicitly supporting students' SRL strategy use.